The choice of tactic for surgical treatment of aortic arch hypoplasia with ventricular septal defect in infants - Ya. P. Truba; V. V. Lazoryshynets; R. I. Sekelyk; I. V. Dziuryi; O. S. Holovenko (Zaporozhye State Medical University, 2020)
Aim: to determine the optimal tactic for surgical correction of aortic arch hypoplasia and ventricular septal defect (VSD) in infants based on the comparison of immediate and follow-up outcomes of one- and two-stage repair. Materials and methods. Between 2011 to 2019, 138 patients under the age of one year underwent surgical repair of aortic arch hypoplasia with VSD in the leading Ukrainina cardiosurgical institutions - National M. Amosov Institute of Cardiovascular Surgery Affilated to National Academy of Medical Sciences of Ukraine and Center for Pediatric Cardiology and Cardiac Surgery. Patients were divided into two groups: group I involved 66 (47.8 %) patients who underwent one-stage repai of aortic arch hypoplasia and VSD, group II included 72 (52.2 %) patients with two-stage repair, consisting of aortic arch reconstruction and pulmonary banding at the first stage, and correction of VSD at the second stage. Results. The total hospital mortality was 3.6 % (n = 5). In group I, hospital mortality was 3.0 % (n = 2), in group II - 4.2 % (n = 3), but this difference is not statistically significant (P > 0.05). Follow-up was from 1 month to 11 years. Mortality rate over follow-up period was 0 %. Aortic arch restenosis developed in 16 (11.6 %) patients: 6 (9.1 %) patients in group I and 10 (13.9 %) patients in group II. There was no statistically significant difference in restenosis development between two groups. Compression of the trachea and left main bronchus developed in two patients of group II (2.8 %). There were no residual VSDs which would need repeated repair. Conclusions. Both one-stage and two-stage tactic for surgical treatment of aortic arch hypoplasia with VSD in infants is effective and safe showing good immediate and long-term follow-up results. The study indicates that one- stage correction is more acceptable in infants with hypoplasia of segment C or all aortic arch segments. Stage tactic can be used in hypoplasia of segments B and A.